Bacterial study of some cosmetic products marketed in Syria - سلوم قيس; مرعي منى (Latakia University Journal -Medical Sciences Series, 2023)
Introduction:Cosmetics or personal care products are popular worldwide and can be easily purchased, with no need for a prescription. This means that these products are not under the same strict regulations as those of prescription medicines. They are mainly applied on the skin or hair, but some, such as toothpastes and mouthwashes, are also used internally. Cosmetics are not intended to permanently alter the physiology of the target organ, although some ‘healthcare’ products may claim medicinal benefits. These include cosmetics that help with conditions such as dandruff, scars, spots and poor gum health. The microbiology of cosmetics is complex due to the wide range of formulations, manufacturing procedures and conditions of consumer use. Objective:The objective of this study is to assess the bacterial quality of some selected brands of cosmetics produced and marketed in our country Syria. Samples and methods: Sixty-five samples of different brands of commercially available products manufactured in Syria were evaluated for their bacterial quality using standard procedures to detect and identify specified microorganisms, these procedures included direct colony count and enrichment culturing. Results:There was no detectable growth in 51 sample cultures. 14 samples tested showed bacterial growth. The predominant bacterial isolates were Staphylococcus aureus in 8 samples and Pseudomonas aeruginosa in 3 samples.